DIMENSI AKHLAK DALAM SHALAT Telaah Teologis-Filosofis - Sehat Sultoni Dalimunthe (Jurnal Pendidikan Islam, 2012)
Akhlak reflects the identity and quality of the individual, society, tribe and nation and even the parameter of dignity of all human civilization throughout the ages. The essence of Islam is akhlak. The concept is stated in the Hadith saying that Allah not merely sent Muhammad SAW except for an important task to edify mankind. Islamic education that focuses on the formation of akhlak is essential. Akhlak-based Islamic education studies and practices good behaviour and teaches students to avoid reprehensible behavior. Theologically, examining the akhlak can be done by using theological and philosophical approaches together. Religion (revelation) from God and philosophy (reason) come also from Allah swt. Methodologically, morals can be studied by using method tajribi (inductive) and method of qiyas (deductive). In didactic, akhlak can be taught, through role models and habituation.